Adult Stem Cells in the Small Intestine Are Intrinsically Programmed with Their Location‐Specific Function. (May 2014) - Middendorp, Sabine; Schneeberger, Kerstin; Wiegerinck, Caroline L.; Mokry, Michal; Akkerman, Ronald D. L.; van, Simone; Clevers, Hans; Nieuwenhuis, Edward E. S.
Abstract Differentiation and specialization of epithelial cells in the small intestine are regulated in two ways. First, there is differentiation along the crypt‐villus axis of the intestinal stem cells into absorptive enterocytes, Paneth, goblet, tuft, enteroendocrine, or M cells, which is mainly regulated by WNT. Second, there is specialization along the cephalocaudal axis with different absorptive and digestive functions in duodenum, jejunum, and ileum that is controlled by several transcription factors such as GATA4. However, so far it is unknown whether location‐specific functional properties are intrinsically programmed within stem cells or if continuous signaling from mesenchymal cells is necessary to maintain the location‐specific identity of the small intestine. Using the pure epithelial organoid technique, we show that region‐specific gene expression profiles are conserved throughout long‐term cultures of both mouse and human intestinal stem cells and correlated with differential Gata4 expression. Furthermore, the human organoid culture system demonstrates that Gata4‐regulated gene expression is only allowed in absence of WNT signaling. These data show that location‐specific function is intrinsically programmed in the adult stem cells of the small intestine and that their differentiation fate is independent of location‐specific extracellular signals. In light of the potential future clinical application of small intestine‐derived organoids, our data imply that it is important to generate GATA4‐positive and GATA4‐negative cultures to regenerate all essential functions of the small intestine. Stem Cells2014;32:1083–1091